PEMANFAATAN ANGGUR LAUT (Caulerpa recemosa) DALAM PEMBUATAN SUP KRIM INSTAN - Dhanang Puspita, Windu Merdekawati, dan Nella Suryani Rahangmetan (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Caulerpa recemosa is one type of seaweed commonly used as a snack in raw form. High water content causes Caulerpa recemosa susceptible to damage. One effort to utilize Caulerpa recemosa is to process it to instant cream soup. The purpose of this study was to process Caulerpa recemosa into instant cream soup and done proximate analysis so as sensory evaluation. The methods done in this research were instant cream soup processing using vacuum drying oven then proximate analysis and sensory evaluation. The results of this research was that instant cream soup produced in this research equipped with green characteristics and seaweed scent. Based on the results of the proximate analysis, the instant cream soup contained water content (5.78%), ash (17.82%), protein (5.74%), fat (17.50%), and carbohydrate (60.87%). Sensory evaluation, visually, and taste showed a significant difference between instant cream soup and control, while texture, aroma and overall acceptance were not significantly different. Instant cream soup Caulerpa recemosa has distinctive characteristics for the colour and aroma that can be as added value, besides it also had good nutritional value and can be accepted by consumers. It could be concluded that Caulerpa recemosa could be processed into instant cream soup and has nutritional value and could be accepted by panelists.Keywords: Caulerpa recemosa, cream soup instant, vacuum drying oven, utilization